Regionalization of the telencephalon in urodele amphibians and its bearing on the identification of the amygdaloid complex - Moreno, Nerea; González, Agustín (Frontiers in Neuroanatomy, 2007)
The brain of urodele amphibians has formed the basis for numerous comparative neuroanatomical studies because its simplified arrangement of neurons and fibers was considered to represent the basic pattern common to all tetrapods. However, on the basis of classical histological techniques many common features shared by the brain of amniotes could not be identified in the anamniotic amphibians. Recently, the combined analysis of the chemoarchitecture and hodology has demonstrated that the brain, and particularly the telencephalon, of anuran amphibians shares all major basic features with amniotes. In the present study, we have conducted a series of immunohistochemical detections for telencephalic regional markers (nitric oxide synthase (NOS), γ-amino butyric acid (GABA), Islet-1 (Isl1), and Nkx2.1) that were useful tools for unraveling telencephalic organization in other vertebrates. In addition, the combination of tract-tracing techniques with dextran amines to demonstrate olfactory secondary centers, hypothalamic projections, and brainstem connections has served to propose subdivisions within the amygdaloid complex. The results of the present analysis of the urodele telencephalon using a multiple approach have demonstrated, among other features, the presence of a ventral pallial region, striatopallidal subdivision in the basal ganglia, and three main components of the amygdaloid complex. Therefore, in spite of its apparently simple organization, within the telencephalon of urodeles it is possible to identify most of the features observed in amniotes and anurans that are only revealed with the use of combined modern techniques in neuroanatomy.